Modified additive for sodium ion secondary battery

By using modified additives of sodium ferromanganate core and carbon coating in the positive electrode material of sodium ion battery, the shortcomings of NFPP and NFM materials in cyclic stability, air stability and interface side reactions are solved, and the performance and life of the battery are significantly improved.

CN119812326APending Publication Date: 2025-04-11QINGHAI NORMAL UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411702350.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-11

Smart Images

  • Figure CN119812326A_ABST
    Figure CN119812326A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion secondary battery modified additive, and relates to the technical field of battery materials. The modified additive for the sodium ion secondary battery comprises an inner core and a carbon wrapping layer wrapping the inner core, the inner core comprises sodium nickel manganese ferrite, the expression of the sodium nickel manganese ferrite is NaFexMnyAzO2, in the expression, x is more than 0 and less than or equal to 0.5, y is more than 0 and less than or equal to 0.5, z is more than 0 and less than or equal to 0.5, x + y + z = 1, the element A in the expression of the sodium nickel manganese ferrite comprises one or more of Ni, Zr, Nb, Mo, Ta, W, Sn, Co, Cu, Zn, Cr, Al, V, Ti and Sb, and the element B in the expression of the sodium nickel manganese ferrite comprises one or more of Ni, Zr, Nb, Mo, Ta, W, Sn, Co, Cu, Zn, Cr and Sb. The mass ratio of the inner core to the carbon wrapping layer is 100: (0.1-5). The sodium ion secondary battery modified additive has the advantages of good cycle stability and excellent high and low temperature performance, and can significantly improve the first coulombic efficiency, the energy density, the high and low temperature performance and the cycle life of secondary batteries such as NFPP batteries and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, in particular to a sodium ion secondary battery modification additive. Background Art

[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and energy storage systems due to their high energy density, long cycle life and good rate performance. However, the limited lithium resources and unstable lithium prices have prompted researchers to look for alternative technologies. Sodium-ion batteries have become an important supplement to lithium-ion batteries because of their abundant resources, low cost and environmental friendliness.

[0003] As a positive electrode material for sodium-ion batteries, NFPP is environmentally friendly: NFPP is an iron-based mixed multi-anion positive electrode material whose constituent elements are harmless to the environment and in line with the current trend of green energy and sustainable development. NFPP has a suitable operating voltage, which helps to improve the energy output efficiency of the battery. Good low-temperature performance: NFPP can still maintain good electrochemical properties in low-temperature environments, which is of great significance for the application of sodium-ion batteries in cold regions.

[0004] NFPP also has some limitations. Poor electronic and ionic conductivity: The irremovable NaFePO4 impurities produced in all synthesis methods lead to poor electronic and ionic conductivity of NFPP, which limits its capacity utilization. Limited diffusion dynamics: The diffusion dynamics of NFPP are limited, which further affects its electrochemical performance. The actual capacity is lower than the theoretical capacity: Due to structural defects, the actual capacity of NFPP is lower than its theoretical capacity, which has become a major difficulty in improving the performance of NFPP. Energy density problem: Compared with lithium-ion batteries, the energy density of sodium-ion batteries is generally low, about only about 1 / 2-2 / 3 of that of lithium batteries, which to a certain extent limits the competitiveness of sodium-ion batteries in application scenarios with higher energy density requirements.

[0005] NFM is a potential layered oxide material for the positive electrode of sodium-ion batteries. Its structure is similar to the NMC (nickel cobalt manganese oxide) material in lithium-ion batteries. This material provides good electrochemical performance through the synergistic effect of transition metals. In order to further improve the performance of NFM, researchers have adopted a variety of modification strategies. For example, by in-situ V modification, V was successfully doped in the bulk. 5+ , improving the electronic conductivity and structural stability of the material, thereby significantly improving the cycle performance. In addition, Cu doping has also been shown to change the electronic structure of NFM and enhance its electrochemical performance. The modified NFM material exhibits ultra-long cycle life and excellent rate performance. For example, after 5000 cycles at a high rate of 10C, the capacity retention rate is still as high as 77.4%. In addition, the Cu-doped NFM material has a very good cycling performance at 20Ag.-1 After 14,000 cycles at a current density of 1.50,000, the capacity retention rate was 80.8%. At the same time, NFM also performs well in low temperature environments. For example, at -40°C, its capacity retention rate can still reach more than 80% of that at room temperature. NFM materials have shown good safety in safety tests such as over-discharge, short circuit, and high temperature.

[0006] In summary, NFM also has many advantages, but it also has some limitations. Poor air stability: NFM materials have poor stability in the air and are easy to react with moisture and carbon dioxide in the air to generate a large amount of residual alkali, such as sodium carbonate and sodium hydroxide. These residual alkalis will cause obvious particles on the surface of the material, affecting the industrial application of the material. Poor cycle stability: During the charge and discharge cycle of NFM materials, complex phase changes will occur due to the deintercalation of Na+, which leads to poor cycle stability of the material. Interface side reactions: When NFM materials circulate in the electrolyte, a series of interface side reactions will occur, such as the decomposition of the electrolyte under high voltage conditions and the induction of HF attack, resulting in irreversible transition metal dissolution and gas release. These interface problems usually lead to irreversible structural damage of the positive electrode material and the generation of cracks in the lattice, which seriously affects the interface stability and electrochemical performance of the layered positive electrode. Gas generation problem: NFM materials are prone to produce a large amount of gas during the cycle, which makes the battery cell more likely to fail, resulting in battery cell gas bloating, and then causing the battery cell to be scrapped.

[0007] In summary, NFPP and NFM each have their own advantages. In the composite battery system, NFM and NFPP can work together as different positive electrode materials to give full play to their respective advantages. For example, NFM can provide a higher initial capacity, while NFPP can maintain a higher capacity retention rate in a low temperature environment. This synergistic effect helps to improve the performance of the entire battery system. Summary of the invention

[0008] In view of the deficiencies of the prior art, the present invention provides a sodium ion secondary battery modification additive, which solves the problems raised in the above background technology.

[0009] To achieve the above objectives, the present invention is implemented by the following technical solutions: a sodium ion secondary battery modification additive, the sodium ion secondary battery modification additive comprising a core and a carbon coating layer covering the core;

[0010] The core includes sodium nickel manganese ferrite, and the sodium nickel manganese ferrite is expressed as:

[0011] NaFe x Mn y A z O2;

[0012] Wherein, 0<x≤0.5, 0<y≤0.5, 0<z≤0.5, x+y+z=1;

[0013] The element A in the expression of sodium nickel manganese ferrite includes one or more of Ni, Zr, Nb, Mo, Ta, W, Sn, Co, Cu, Zn, Cr, Al, V, Ti and Sb;

[0014] The mass ratio of the inner core to the carbon wrapping layer is 100:(0.1-5).

[0015] A further improvement of the technical solution of the present invention is that it also has at least one of the following three settings:

[0016] The thickness of the carbon coating layer is controlled to be 0.1nm to 100nm;

[0017] The core particle size D50 is controlled at 1 μm to 8 μm;

[0018] The specific capacity of the sodium ion secondary battery modification additive is ≥105 mAh / g.

[0019] A further improvement of the technical solution of the present invention is that it also provides a preparation method for a sodium ion secondary battery modification additive, comprising the following specific steps:

[0020] The iron source, manganese source and A source are weighed and dissolved in water, and a mixed solution of sodium hydroxide and ammonia water is slowly added dropwise while stirring until the pH value is 11.5, and the pH value is kept greater than 11 while stirring in a water bath at 40° C. for 4 hours, and the mixture is allowed to stand, filtered, washed with alcohol, and dried. After crushing, the mixture is obliquely mixed with sodium salt powder, calcined at 900° C. for 16 hours, and a carbon source and a grinding aid are added for ball milling (ball milling speed 300-500 rpm, ball milling time 1-8 hours, ball milling medium (vacuum ball milling), ball-to-material ratio 1:1-10:1), and calcined at 440° C. for 4 hours under a nitrogen atmosphere to obtain a sodium ion secondary battery modification additive.

[0021] A further improvement of the technical solution of the present invention is that the grinding aid includes one or more of ethanol, cyclohexane, ethyl acetate and acetone.

[0022] A further improvement of the technical solution of the present invention is that the mass ratio of the positive electrode additive, the carbon source and the grinding aid is 100:(80-150):(20%-40%).

[0023] A further improvement of the technical solution of the present invention is that the temperature of the second step sintering treatment is 350° C. to 550° C. and the time is 1 h to 6 h.

[0024] A further improvement of the technical solution of the present invention is that: the iron source includes one or more of ferrous chloride, ferrous sulfate, and ferrous nitrate; the sodium source includes one or more of sodium chloride, sodium hydroxide, sodium carbonate, and sodium oxide; the carbon source includes one or more of PEG200, PEG800, PEG2000, and PVP (K30); the manganese source includes one or more of manganese chloride, manganese sulfate, and manganese nitrate; the A source includes one or more of chloride, fluoride, sulfate, nitrate, and ethanolate of the A element; and the molar ratio of the sodium source, the iron source, the A source, and the B source is 1:(0-0.5):(0-0.5):(0-0.5).

[0025] A further improvement of the technical solution of the present invention is that the sodium ion secondary battery modification additive is applied to a positive electrode plate, the positive electrode plate includes a positive electrode collector, and a positive electrode active layer covering at least one surface of the positive electrode collector, the positive electrode active layer also includes a positive electrode active material, and the mass ratio of the positive electrode active material to the additive is 100:(50~150).

[0026] Compared with the prior art, the beneficial effects of the present invention are: the sodium ion secondary battery modified additive has the advantages of good cycle stability and excellent high and low temperature performance, and can significantly improve the first coulomb efficiency, energy density, high and low temperature performance and cycle life of secondary batteries such as NFPP batteries;

[0027] In addition, the carbon coating on the surface of the inner core can effectively increase the conductivity of the material, while stabilizing the material structure, reducing the impact of electrolyte components on the material structure, and inhibiting the occurrence of side reactions, thereby improving the performance of the positive electrode additive. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 a is the electrical performance data of NFPP positive electrode sodium ion battery at different sub-zero temperatures;

[0029] Figure 1 b is the electrical performance data of the NaFMN positive electrode sodium ion additive battery at different sub-zero temperatures of the present invention;

[0030] Figure 1 c is the electrical performance data of the battery prepared when the ratio of the positive electrode sodium ion additive to NPFF is 1:1 at different sub-zero temperatures;

[0031] Figure 2 a is the electrical performance data of NFPP positive electrode sodium ion battery at different above zero temperatures;

[0032] Figure 2 b is the electrical performance data of the NaFMN positive electrode sodium ion additive battery at different above zero temperatures of the present invention;

[0033] Figure 2 c is the electrical performance data of the battery prepared by the positive electrode sodium ion additive (NaFMN) of the present invention and NFPP 1:1 at different above zero temperatures;

[0034] Figure 3 The relationship between the cycle number and mass specific capacity of the three electrode materials NFPP, NaFMN, and NaFMN:NFPP (1:1) at -40°C and 45°C.

[0035] Figure 4 is the synthetic route of NFM of the present invention;

[0036] Figure 5 a is the XRD picture of the NFPP;

[0037] Figure 5 b is the XRD picture of NaFMN described in the present invention;

[0038] Figure 5 c is the XRD picture of the mixture of NaFMN and NFPP in the ratio of 1:1 described in the present invention;

[0039] Figure 5 d is a SEM image of the NFPP;

[0040] Figure 5 e is a SEM picture of NaFMN described in the present invention;

[0041] Figure 5 f is a SEM picture of a 1:1 mixture of NaFMN and NFPP according to the present invention;

[0042] Figure 6 a is a picture of the specific capacity and voltage platform of the NFPP and NaFMN and the mixture of the two materials at a ratio of 1:1, 1:2, and 2:1;

[0043] Figure 6 b is a graph showing the cycle number, specific capacity, and coulombic efficiency of the NFPP and NaFMN and the 1:1 mixture of the two materials described in the present invention;

[0044] Figure 6 c is a graph showing the cycle number and specific capacity of the NFPP and NaFMN and a 1:1 mixture of the two materials at different current densities;

[0045] Figure 6 d is a graph of specific capacity and voltage at different current densities of a 1:1 mixture of NFPP and NaFMN described in the present invention. DETAILED DESCRIPTION

[0046] Various exemplary embodiments, features and aspects of the present application will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0047] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0048] In addition, in order to better illustrate the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In some examples, methods, means, and elements well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present application.

[0049] The present invention provides a sodium ion secondary battery modification additive, the sodium ion secondary battery modification additive comprising a core and a carbon coating layer covering the core;

[0050] The core includes sodium nickel manganese ferrite, and the sodium nickel manganese ferrite is expressed as:

[0051] NaFe x Mn y A z O2;

[0052] Wherein, 0<x≤0.5, 0<y≤0.5, 0<z≤0.5, x+y+z=1;

[0053] The element A in the expression of sodium nickel manganese ferrite includes one or more of Ni, Zr, Nb, Mo, Ta, W, Sn, Co, Cu, Zn, Cr, Al, V, Ti and Sb;

[0054] The mass ratio of the inner core to the carbon wrapping layer is 100:(0.1-5).

[0055] Also has at least one of the following three settings:

[0056] The thickness of the carbon coating layer is controlled to be 0.1nm to 100nm;

[0057] The core particle size D50 is controlled at 1 μm to 8 μm;

[0058] The specific capacity of the sodium ion secondary battery modification additive is ≥105 mAh / g.

[0059] In the technical solution of the embodiment of the present application, the core of the positive electrode additive is modified NaFe x Mn y Az O2(NFM), and simultaneously regulated the sodium iron manganese ratio and the amount of element A doped in NFM. The doping effect of the material was explored by changing the iron manganese ratio and the amount of element A added. Finally, it was determined that NaFexMnyAzO2(NFM) with certain x, y, and z values ​​greatly improved the high and low temperature performance of NFPP. The NFM material doped with element A has a more stable lattice structure and inhibits the occurrence of adverse phase change phenomena, which is specifically manifested as excellent cycle performance.

[0060] At the same time, the carbon coating on the surface of the NFM core can effectively increase the conductivity of the material, stabilize the material structure, reduce the impact of electrolyte components on the material structure, and inhibit the occurrence of side reactions, thereby improving the performance of the positive electrode additive.

[0061] Similarly, if the quality of the carbon coating layer is low, it will affect the coating uniformity of the carbon coating layer and the protection effect on the core is poor; if the quality of the carbon coating layer is high, it will cause the electrical performance of the positive electrode additive to decline; controlling the mass ratio of the core and the carbon coating layer within the range of 100: (0.1-5) can ensure that the carbon coating layer forms a good coating effect on the surface of the core without adversely affecting the electrical performance of the positive electrode additive. Therefore, the positive electrode additive provided by the present application has the advantages of good cycle stability and excellent high and low temperature performance, which can significantly improve the first coulomb efficiency, energy density, high and low temperature performance and cycle life of secondary batteries such as NFPP batteries.

[0062] In the first embodiment, the element A is Ni.

[0063] In this embodiment, element A is a transition metal element such as Ni, which can effectively change the properties of the lattice, thereby enhancing the lattice stability of the material, while inhibiting adverse phase change phenomena and reducing volume changes caused by phase change, thereby improving the cycle performance of the battery.

[0064] Example 2, the preparation of the sodium ion secondary battery modification additive comprises the following specific steps: weighing an iron source, a manganese source and a source A and dissolving them in water, slowly adding a mixed solution of sodium hydroxide and ammonia water to pH = 11.5 while stirring, keeping the pH > 11 while stirring in a water bath at 40°C for 4 hours, standing, filtering, washing with alcohol, drying, crushing and mixing obliquely with sodium salt powder, calcining at 900°C for 16 hours, adding a carbon source and a grinding aid for ball milling, the ball milling speed is 300-500 rpm, the ball milling time is 1-8 hours, the ball milling medium, the ball-to-material ratio is 1:1-10:1, and calcining at 440°C for 4 hours under a nitrogen atmosphere to obtain a sodium ion secondary battery modification additive.

[0065] In the technical solution of the embodiment of the present application, the positive electrode additive has good cycle stability and excellent high and low temperature performance, and a green solvent is selected in the preparation process, which has little pollution to the environment.

[0066] Therefore, the grinding aid includes one or more of ethanol, cyclohexane, ethyl acetate and acetone.

[0067] The mass ratio of the positive electrode additive, the carbon source and the grinding aid is 100:(80-150):(20%-40%).

[0068] The temperature of the second step sintering treatment is 350° C. to 550° C., and the time is 1 h to 6 h.

[0069] The iron source includes one or more of ferrous chloride, ferrous sulfate, and ferrous nitrate; the sodium source includes one or more of sodium chloride, sodium hydroxide, sodium carbonate, and sodium oxide; the carbon source includes one or more of PEG200, PEG800, PEG2000, and PVP (K30); the manganese source includes one or more of manganese chloride, manganese sulfate, and manganese nitrate; the A source includes one or more of chloride, fluoride, sulfate, nitrate, and ethanolate of the A element; the sodium source, the iron source, and the A source refer to Figure 4 , Figure 5 In the first aspect, an embodiment of the present application provides a method for preparing a NFM material.

[0070] Please refer to Figure 5 b. Figure 5 e. A element is a transition metal element such as Ni, and the XRD and SEM images when x=y=z=1 / 3 are shown. As shown in the figure, NFM is blocky, with good uniformity and high consistency. This is closely related to the fact that Ni doping can effectively change the properties of the lattice, thereby enhancing the lattice stability of the material, and the molar ratio of the B source is 1:(0-0.5):(0-0.5):(0-0.5);

[0071] Please refer to Figure 4 In the second aspect, the present application provides a NaFe x Mn y A z The preparation method of O2 material is as follows, wherein each material is for example only and can be replaced by the above materials;

[0072] The following specific preparation is carried out to verify its performance; the test group uses the following preparation scheme:

[0073] Weigh 0.05 mol of ferrous sulfate, 0.05 mol of nickel sulfate, and 0.05 mol of manganese sulfate to dissolve, then stir in a water bath at 40°C, and slowly add a mixture of 90% NaOH and 10% ammonia water until the pH reaches 11.5, stir for 4 hours, then let stand, filter, wash with alcohol, dry, add 0.15 mol of sodium carbonate powder after crushing, mix obliquely, then calcine at 900°C for 10 hours, then add an equal mass of PEG-2000 and an appropriate amount of ethanol for ball milling, and then calcine at 440°C for 4 hours under a nitrogen atmosphere to obtain a finished product;

[0074] Weigh 0.06 mol of ferrous sulfate, 0.06 mol of nickel sulfate, and 0.03 mol of manganese sulfate to dissolve, then stir in a water bath at 40°C, slowly add a mixture of 90% NaOH and 10% ammonia water until the pH reaches 11.5, stir for 4 hours, then let stand, filter, wash with alcohol, dry, add 0.15 mol of sodium carbonate powder after crushing, mix obliquely, then calcine at 900°C for 16 hours, then add an equal mass of PEG-2000 and an appropriate amount of ethanol for ball milling, and then calcine at 440°C for 4 hours under a nitrogen atmosphere to obtain a finished product;

[0075] Weigh 0.05 mol of ferrous sulfate, 0.05 mol of nickel sulfate, and 0.05 mol of manganese sulfate to dissolve, then stir in a 40°C water bath, and slowly add a mixture of 90% NaOH and 10% ammonia water until the pH reaches 11.5, stir for 4 hours, then let stand, filter, wash with alcohol, and dry, add 0.15 mol of sodium carbonate powder after crushing and mix obliquely, then calcine at 900°C for 16 hours, then add 80% PEG-2000 by weight of the calcined powder and an appropriate amount of ethanol for ball milling, and then calcine at 440°C for 4 hours under a nitrogen atmosphere to obtain a finished product.

[0076] First, weigh 2 grams of NFPP and 4 grams of NFM and mix them, and test their XRD, SEM high and low temperature and cycle performance. Then weigh 4 grams of NFPP and 2 grams of NFM and mix them, and test their XRD, SEM high and low temperature and cycle performance. Finally, weigh equal masses of NFPP and NFM and mix them, and test their XRD, SEM high and low temperature and cycle performance.

[0077] The control test group was prepared by weighing 0.05 mol of ferrous sulfate, 0.05 mol of nickel sulfate, and 0.05 mol of manganese sulfate to dissolve, then stirring in a 40°C water bath, and slowly adding a mixture of 90% NaOH and 10% ammonia water until the pH reached 11.5, stirring for 4 hours, then standing, filtering, washing with alcohol, drying, and adding 0.15 mol of sodium carbonate powder after crushing, and then calcining at 900°C for 16 hours, then adding an equal mass of PEG-2000 and an appropriate amount of ethanol for ball milling, and then calcining at 440°C for 4 hours under a nitrogen atmosphere to obtain a finished product.

[0078] A certain amount of NFPP and an equal amount of NFM were weighed to test their XRD, SEM high and low temperature and cycle performances respectively.

[0079] The results are shown in the attached figure. The XRD has no impurity peaks, the peaks are sharp, the crystallinity is good, the SEM image particles are uniform and there is no obvious debris. The positive electrode plate uses the Blue Electric test system to test the material's gram capacity and high and low temperature cycle performance.

[0080] Embodiment 3, based on embodiment 1 and embodiment 2, the sodium ion secondary battery modification additive is applied to a positive electrode plate, the positive electrode plate includes a positive electrode collector, and a positive electrode active layer covering at least one surface of the positive electrode collector, the positive electrode active layer also includes a positive electrode active material, and the mass ratio of the positive electrode active material to the additive is 100: (50~150), the embodiment of the present application provides a positive electrode plate, the positive electrode material NFPP 46%; PVDF 4%; CNT 4%; additive 46%, the positive electrode plate contains the above-mentioned sodium ion positive electrode additive material, and thus has the advantage of higher specific capacity.

[0081] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A sodium ion secondary battery modification additive, characterized in that: The sodium ion secondary battery modification additive comprises a core and a carbon coating layer covering the core; The core includes sodium nickel manganese ferrite, and the sodium nickel manganese ferrite is expressed as: <h2 style=";text-align:left;direction:ltr">NaFe<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> A<h2 style=";text-align:left;direction:ltr"> z <h2 style=";text-align:left;direction:ltr"> O2; Wherein, 0<x≤0.5, 0<y≤0.5, 0<z≤0.5, x+y+z=1; The element A in the expression of sodium nickel manganese ferrite includes one or more of Ni, Zr, Nb, Mo, Ta, W, Sn, Co, Cu, Zn, Cr, Al, V, Ti and Sb; The mass ratio of the inner core to the carbon wrapping layer is 100:(0.1-5).

2. A sodium ion secondary battery modifying additive according to claim 1, characterized in that: Also has at least one of the following three settings: The thickness of the carbon coating layer is controlled to be 0.1nm to 100nm; The core particle size D50 is controlled at 1 μm to 8 μm; The specific capacity of the sodium ion secondary battery modification additive is ≥105 mAh / g.

3. A sodium ion secondary battery modifying additive according to claim 2, characterized in that: The preparation of the sodium ion secondary battery modification additive comprises the following specific steps: The iron source, manganese source and A source were weighed and dissolved in water, and a mixed solution of sodium hydroxide and ammonia water was slowly added dropwise while stirring until the pH value was 11.

5. The mixture was stirred in a water bath at 40°C for 4 hours while the pH value was kept greater than 11. The mixture was allowed to stand, filtered, washed with alcohol, and dried. After crushing, the mixture was obliquely mixed with sodium salt powder, calcined at 900°C for 16 hours, a carbon source and a grinding aid were added for ball milling, and the mixture was calcined at 440°C for 4 hours under a nitrogen atmosphere to obtain a sodium ion secondary battery modification additive.

4. A sodium ion secondary battery modifying additive according to claim 3, characterized in that: The grinding aid includes one or more of ethanol, cyclohexane, ethyl acetate and acetone.

5. The sodium ion secondary battery modifying additive according to claim 3, characterized in that: The mass ratio of the positive electrode additive, the carbon source and the grinding aid is 100:(80-150):(20%-40%).

6. The sodium ion secondary battery modifying additive according to claim 3, characterized in that: The temperature of the second step sintering treatment is 350° C. to 550° C., and the time is 1 h to 6 h.

7. The sodium ion secondary battery modifying additive according to claim 3, characterized in that: The iron source includes one or more of ferrous chloride, ferrous sulfate, and ferrous nitrate, the sodium source includes one or more of sodium chloride, sodium hydroxide, sodium carbonate, and sodium oxide, the carbon source includes one or more of PEG200, PEG800, PEG2000, and PVP (K30), the manganese source includes one or more of manganese chloride, manganese sulfate, and manganese nitrate, the A source includes one or more of chloride, fluoride, sulfate, nitrate, and ethanolate of the A element, and the molar ratio of the sodium source, the iron source, the A source, and the B source is 1:(0-0.5):(0-0.5):(0-0.5).

8. The sodium ion secondary battery modifying additive according to claim 1, characterized in that: The sodium ion secondary battery modification additive is applied to a positive electrode plate, which includes a positive electrode collector and a positive electrode active layer covering at least one surface of the positive electrode collector, wherein the positive electrode active layer also includes a positive electrode active material, and the mass ratio of the positive electrode active material to the additive is 100:(50-150).

Citation Information

Patent Citations

  • Positive electrode sodium supplement additive and preparation method and application thereof

    CN116111072A

  • O3-type nickel-iron-manganese-based low-nickel single-crystal positive electrode material as well as preparation method and application thereof

    CN116864651A

  • Carbon-coated hollow polyhedral sodium ferro-nickel manganate positive electrode material and preparation method thereof

    CN117069161A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117457885A

  • Preparation method of high-capacity magnesium ion doped lithium-sodium composite sodium ion battery layer oxygen positive electrode material

    CN117747775A